Uric acid, joint morbidity, and streptococcal antibodies in Maori and European teenagers. Rotorua Lakes study 3. Issue 4 (August 1975) - Stanhope, J M; Prior, I A
Abstract : Two hundred and ninety-four New Zealand secondary school students were examined by questionnaire, and physical and biochemical methods. The sample contained almost equal numbers of Maoris and Europeans. The findings related to joint conditions are presented. Past injury and rheumatic disease accounted for some of the reported morbidity, but no important sex or race differences in these factors emerged. There were, however, significant differences in serum uric acid levels with the Maori having higher levels than the Europeans. A significant correlation with body mass was present in both race and sex groups but a correlation with haemoglobin was present only in the European females. While hyperuricaemia was not associated with morbidity in this young sample, ethnic differences anticipated the higher prevalence of gout already observed in Maori men.